Case for diagnosis. A bluish nodule on the scalp - Sylvia Aide Martinez-Cabriales; Ivette Miranda-Maldonado; Jorge Ocampo-Candiani (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Acrospiroma, also known as hidradenoma, is a rare cutaneous tumor that has several histological characteristics. As a consequence, a high index of suspicion is necessary for its diagnosis. Here we report a case that illustrates the importance of a good clinical-pathologic correlation in order to recognize this disease.